(untitled) (Communications in Inorganic Synthesis, 2014)
The dibutyltin complex of 2,4-dichloro-5- fluorobenzoic acid, [(2,4-Cl2 -5-FC6 H2 C(O)OSnBu2 )2 O]2 (Bu = CH2 CH2 CH2 CH3 ) (1 ), has been synthesized and characterized by elemental analysis, FT-IR, 119 Sn NMR spectroscopy, and Xray single crystal diffraction. Compound 1 is a centrosymmetric dimmer with two distinct types of carboxylate moieties and tin atoms with distorted trigonal bipyramidal geometries. The in vitroÂ anti-tumor activity of 1 against two human tumor cell lines was found to be higher than that for cis-platin [cis diaminedichloroplatinum( II)] used clinically. Supporting information : FT-IR, 119 Sn NMR, X-Ray, Proliferation inhibitory rate, Cif file.